Rapid Downregulation of DAB2 by Toll-Like Receptor Activation Contributes to a Pro-Inflammatory Switch in Activated Dendritic Cells - Figliuolo da Paz, Vanessa; Jamwal, Deepa R.; Gurney, Michael; Midura-Kiela, Monica; Harrison, Christy A.; Cox, Christopher; Wilson, Jean M.; Ghishan, Fayez K.; Kiela, Pawel R. (Frontiers in Immunology, 2019)
Dendritic cells (DCs) are pivotal in regulating tolerogenic as well as immunogenic responses against microorganisms by directing both the innate and adaptive immune response. In health, phenotypically different DC subsets found in the gut mucosa are maintained in their tolerogenic state but switch to a pro-inflammatory phenotype during infection or chronic autoinflammatory conditions such as inflammatory bowel disease (IBD). The mechanisms that promote the switch among the mucosal DCs from a tolerogenic to an immunogenic, pro-inflammatory phenotype are incompletely understood. We hypothesized that disabled homolog 2 (DAB2), recently described as a negative regulator of DC immunogenicity during their development, is regulated during intestinal inflammation and modulates mucosal DC function. We show that DAB2 is highly expressed in colonic CD11b+CD103- DCs, a subset known for its capacity to induce inflammatory Th1/Th17 responses in the colon, and is downregulated predominantly in this DC subset during adoptive T cell transfer colitis. Administration of Dab2-deficient DCs (DC2.4Dab2-/- cells) modulated the course of DSS colitis in wild-type mice, enhanced mucosal expression of Tnfa, Il6 and Il17a, and promoted neutrophil recruitment. In bone-marrow derived dendritic cells (BMDC), DAB2 expression correlated with CD11b levels and DAB2 was rapidly and profoundly inhibited by TLR ligands in a TRIF- and MyD88-dependent manner. The negative modulation of DAB2 was biphasic, initiated with a quick drop in DAB2 protein, followed by a sustained reduction in Dab2 mRNA. DAB2 downregulation promoted a more functional and activated DC phenotype, reduced phagocytosis and increased CD40 expression after TLR activation. Furthermore, Dab2 knockout in DCs inhibited autophagy and promoted apoptotic cell death. Collectively, our results highlight the immunoregulatory role for DAB2 in the intestinal dendritic cells and suggest that DAB2 downregulation after microbial exposure promotes their switch to an inflammatory phenotype.